(untitled) - Richards, Annette (Cambridge, 2001)
This book brings together music and visual arts, especially the art of landscape gardening, in the context of late eighteenth- and early nineteenth-century English and German culture. The aesthetic of the picturesque, derived from the controlled wilderness of the landscape garden, provided writers on music with a language in which to describe the musical genre of the free fantasia, and the picturesque emerges here as a vital means for understanding the fantastical elements in the music of C. P. E. Bach, Haydn, and Beethoven.
Keywords: Music,Âm nhạc,Art and music,Nghệ thuật và âm nhạc; History and criticism,Lịch sử và bình luận; 18th century,Thế kỷ thứ 18; Europe,Châu Âu